AN ANALYSIS OF THE APPLICATION OF PROBLEM BASED LEARNING (PBL) MODEL IN MATHEMATICS FOR ELEMENTARY SCHOOL STUDENTS - Sarnoko, Sarnoko; Asrowi, Asrowi; Gunarhadi, Gunarhadi; Usodo, Budi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
The problem-based learning model remains an innovative model that is often implemented for learning in the 21st century, as an effort to achieve students' soft skill competencies. Therefore, the purpose of this study is to identify the necessary learning model in Mathematics at Girimarto District Elementary Schools and to analyze the application of the problem-based learning model at these schools. This research is classified as descriptive quantitative research, and it involves a random sample of 106 students and 10 elementary school teachers in the Girimarto area. The data collection technique used is non-test, specifically through the use of questionnaires. The data obtained from the questionnaires are analyzed descriptively using percentages to depict the research findings. The study highlighted a suboptimal implementation of the Problem-Based Learning (PBL) model in Girimarto District, with only 44.94% of the sample demonstrating mastery of critical thinking, 35.67% exhibiting creative reasoning, and 25.09% performing analytical thinking. This indicates a lack of High Order Thinking Skills (HOTS)-based learning among teachers. Various obstacles were identified, including student passivity, fear, and unfamiliarity with the PBL model. Interviews and observations further revealed that many teachers had not fully grasped the concept of PBL. The study emphasizes the need to address these obstacles to enhance PBL implementation and improve Mathematics learning outcomes in Girimarto District Elementary Schools. The implications of these findings underscore the necessity of addressing these barriers to enhance the implementation of PBL and improve Mathematics learning outcomes in Girimarto Elementary School.